(untitled) (Bangladesh Journal of Botany, 2020)
The role of Trichoderma harzianum, Bacillus subtilis and Pseudomonas fluorescens (alone and in combination) in inducing systemic resistance in chickpea exposed to Fusarium oxysporum ciceris was investigated. Chickpea seed (var. Radhey) treatment with Trichoderma harzianum, Bacillus subtilis and Pseudomonas fluorescens alone and in combination on the germination, wilt incidence, plant growth promotion, yield, production of chlorophyll, protein, peroxidase, polyphenol oxidase and total phenol content was recorded. The results of in vitro studies revealed better performances of treatment T6 (Seed treatment with 1% Trichoderma harzianum + 2% Pseudomonas fluorescens + 2% Bacillus subtilis in combination). This treatment significantly reduced wilt incidence and increased germination, root length, shoot length, and yield as compared to untreated control. Treatment T6 also induced 1.4 per cent increase in peroxidase, 1.6 in polyphenol oxidase and 2.3 in total phenol in chickpea during pathogenesis by F. oxysporum ciceris f. sp. Similarly, 1.9% increase in chlorophyll and protein was recorded with the treatment T6 as compared to control. Present investigations will be helpful in formulating novel bioformulations using fungal and bacterial bioagents to control wilt in chickpea.